The prognostic value of right ventricular long axis strain in non-ischaemic dilated cardiomyopathies using standard cardiac magnetic resonance imaging - Arenja, Nisha; Riffel, Johannes; Halder, Manuel; Djiokou, Charly N.; Fritz, Thomas; André, Florian; Siepen, Fabian aus dem; Zelniker, Thomas; Meder, Benjamin; Kayvanpour, Elham; Korosoglou, Grigorios; Katus, Hugo; et al. (European radiology, 2017)
OBJECTIVE: To investigate the association of right ventricular long axis strain (RV-LAS), a parameter of longitudinal function, with outcome in patients with non-ischaemic dilated cardiomyopathy (NIDCM). METHODS: In 441 patients with NIDCM, RV-LAS was analysed retrospectively by measuring the length between the epicardial border of the left ventricular apex and the middle of a line connecting the origins of the tricuspidal valve leaflets in end-diastole and end-systole on non-contrast standard cine sequences. RESULTS: The primary endpoint (cardiac death or heart transplantation) occurred in 41 patients, whereas 95 reached the combined endpoint (including cardiac decompensation and sustained ventricular arrhythmias) during a median follow-up of 4.2 years. Kaplan-Meier survival curves showed a poor outcome in patients with RV-LAS values below -10% (log-rank, p < 0.0001). In a risk stratification model RV-LAS improved prediction of outcome in addition to RV ejection fraction (RVEF) and presence of late gadolinium enhancement. Assessment of RV-LAS offered incremental information compared to clinical symptoms, biomarkers and RVEF. Even in the subgroup with normal RVEF (>45%, n = 213) reduced RV-LAS was still associated with poor outcome. CONCLUSION: Assessment of RV-LAS is an independent indicator of outcome in patients with NIDCM and offers incremental information beyond clinical and cardiac MR parameters. KEY POINTS: • Impaired right ventricular longitudinal function (RV-LAS) is associated with poorer cardiac outcomes. • Poor outcome is associated with decreased RV-LAS even in patients with RVEF >45%. • Addition of RV-LAS to known risk factors enhances the power prognostic information.